2020
DOI: 10.1093/mnras/staa651
|View full text |Cite
|
Sign up to set email alerts
|

Classical Nova Carinae 2018: discovery of circumbinary iron and oxygen

Abstract: We present time-lapse spectroscopy of a classical nova explosion commencing 9 d after discovery. These data reveal the appearance of a transient feature in Fe ii and [O i]. We explore different models for this feature and conclude that it is best explained by a circumbinary disc shock-heated following the classical nova event. Circumbinary discs may play an important role in novae in accounting for the absorption systems known as transient heavy element absorption (THEA), the transfer of angular momentum, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Nova V906 Car (ASASSN-18fv) was discovered in eruption in March 2018 by ASAS-SN (Stanek et al 2018) and peaked at ∼5 mag in the optical. The nova was observed extensively from radio to γ-ray and has already been the topic of multiple studies (Molaro et al 2020;McLoughlin et al 2020;Aydi et al 2020;Pavana et al 2020;Wee et al 2020;Sokolovsky et al 2020). Aydi et al (2020) detected a correlation between flares in its optical and γ-ray light curves, which led them to conclude that shocks are the source of a substantial fraction of the nova optical luminosity (in contrast to the standard picture of a nuclear-burning white dwarf powering the bolometric luminosity).…”
Section: The Spectral Evolution Of Nova V906 Carmentioning
confidence: 99%
See 1 more Smart Citation
“…Nova V906 Car (ASASSN-18fv) was discovered in eruption in March 2018 by ASAS-SN (Stanek et al 2018) and peaked at ∼5 mag in the optical. The nova was observed extensively from radio to γ-ray and has already been the topic of multiple studies (Molaro et al 2020;McLoughlin et al 2020;Aydi et al 2020;Pavana et al 2020;Wee et al 2020;Sokolovsky et al 2020). Aydi et al (2020) detected a correlation between flares in its optical and γ-ray light curves, which led them to conclude that shocks are the source of a substantial fraction of the nova optical luminosity (in contrast to the standard picture of a nuclear-burning white dwarf powering the bolometric luminosity).…”
Section: The Spectral Evolution Of Nova V906 Carmentioning
confidence: 99%
“…Recently, McLoughlin et al (2020) suggested the presence of a circumbinary disk rich with Fe and O in nova V906 Car. Their evidence consists of particular emission lines of Fe ii at 5991 Å (46), 6432 Å (40), 6456 Å (74), and 6516 Å (40), in addition to [O i] 6300 Å, which are characterized by double-peaked profiles and mod-est expansion velocities (FWZI ≈ 900 km s −1 ).…”
Section: Circumbinary Material?mentioning
confidence: 99%
“…The designation of phases for the optical spectroscopic progression of classical novae has typically focused on relatively early-time absorption lines to elucidate what is happening specifically along the line-of-sight to the eruption (McLaughlin 1956). However, a full understanding of the nature and evolution of the classical nova phenomenon necessitates sustained time-resolved studies beyond this regime.…”
Section: Discussionmentioning
confidence: 99%
“…They were first proposed by Williams et al (2008) to originate in a circumbinary disk, fed by an outflow from the companion star. Adding to this McLoughlin et al (2020) arrive at the conclusion of the existence of circumbinary Fe and O for the V906 Car system and claim this reservoir may provide the origin of the THEA lines. The argument for the spectral features not originating in the shell itself is from the lower velocities observed.…”
Section: Introductionmentioning
confidence: 87%